Monte Carlo Solution of High Electric Field Hole Transport Processes in Avalanche Amorphous Selenium - Mukherjee, Atreyo; Vasileska, Dragica; Akis, John; Goldan, Amir H (ACS omega, 2021)
Amorphous selenium lacks the structural long-range order present in crystalline solids. However, the stark similarity in the short-range order that exists across its allotropic forms, augmented with a shift to non-activated extended-state transport at high electric fields beyond the onset of impact ionization, allowed us to perform this theoretical study, which describes the high-field extended-state hole transport processes in amorphous selenium by modeling the band-transport lattice theory of its crystalline counterpart trigonal selenium. An in-house bulk Monte Carlo algorithm is employed to solve the semiclassical Boltzmann transport equation, providing microscopic insight to carrier trajectories and relaxation dynamics of these non-equilibrium “hot” holes in extended states. The extended-state hole–phonon interaction and the lack of long-range order in the amorphous phase is modeled as individual scattering processes, namely acoustic, polar and non-polar optical phonons, disorder and dipole scattering, and impact ionization gain, which is modeled using a power law Keldysh fit. We have used a non-parabolic approximation to the density functional theory calculated valence band density of states. To validate our transport model, we calculate and compare our time of flight mobility, impact ionization gain, ensemble energy and velocity, and high field hole energy distributions with experimental findings. We reached the conclusion that hot holes drift around in the direction perpendicular to the applied electric field and are subject to frequent acceleration/deceleration caused by the presence of high phonon, disorder, and impurity scattering. This leads to a certain determinism in the otherwise stochastic impact ionization phenomenon, as usually seen in elemental crystalline solids.